Contribuição ao conhecimento da fauna helmintológica do Anu Branco (Guira Guira (G. M.)) - Rodrigues, Sônia Sodré (1980)
In this work 95 samples of helminths recovered from Guira guira (Gm.), deposited in the Oswaldo Cruz Helminthological Collection are studied. 91, 8% of the hosts were parasited and the highest infection level was due to the nematodes, followed by the acanthocephalans, trematodes and cestodes. Aprocta brevipenis sp. n., represented by a nematode recovered from eye socket is here proposed. The following species were also studied: Athesmia terolecithodes (Braun, 1899), Echinostoma uncatum Dietz, 1909, Eumegacetes medioximus Braun, 1901, Tanaisia magnicolica Freitas, 1951, Oxyspirura cruzi Rodrigues, 1962, Cyrnea semilunaris (Molin, 1860), Torquatella crotophaga Williams, 1929; Skrjabinura spiralis Gnedina, 1933, Subulura forcipata (Rudolphi, 1819), Anomotaenia mutabilis (Rudolphi, 1819) and Centrorhynchus tumidulus (Rudolphi, 1819). As new host records are redescribed Cyrnea semilunaris (Molin, 1860), Torquatella crotophaga Williams, 1929 and Skrjabinura spiralis Gnedina, 1933 and the latter two species occurring in Brazil for the first time. Oxyspirura anacanthura (Molin, 1860) refered by STRACHAN (1957) in Guira guira (Gm.) from Central Brazil Region is also studied.